Changes in Intimacy and Sexuality During the COVID-19 Pandemic: A Qualitative Analysis of Data from a Survey on Partnered Individuals in Eight European Countries - Löfgren, Charlotta; Elmerstig, Eva; Schröder, Johanna; Chollier, Marie; Mehulić, Jasmina; de Graaf, Hanneke; Klapilova, Katerina; Tavares, Inês; Briken, Peer; Köse, Özlem; Nobre, Pedro; Štulhofer, Aleksandar (Sexuality & culture, 2023)
This qualitative study explores experiences of intimacy and sexuality during the first phase of the COVID-19 pandemic of 3357 participants from Croatia, the Czech Republic, the Netherlands, France, Germany, Portugal, Sweden, and Turkey. Data were collected through open-ended questions within a survey on sexuality during the pandemic. Based on a reflexive thematic analysis three themes occurred. The first theme No change was described by 41% when summarizing their sex life during the pandemic. The second theme Positive change was experienced by 25%, and the third theme Negative change by 21%. An overarching theme then emerged as: "Still the same trajectories, but the pandemic could be a catalyst for improved or worsened sex- life." For those intimate partnered individuals who already had problems with intimacy and sexuality before the COVID-19 pandemic it seemed to remain the same or deteriorated throughout the pandemic. For those with positive experiences of intimacy and sexuality before the COVID-19 pandemic it remained the same or improved throughout the pandemic. These findings are relevant for researchers and clinicians in developing preventive and supportive interventions in the context of crisis and social isolation.
Keywords: Sexual health; COVID-19; Reflexive thematic analysis; Intimacy; Adults; Relationship satisfaction